Listening to the Lived Experience of Black People in Italy. Subjectivity, Digital Representation, and Identity - Pomella, Andrea Ruben (Antropologia Pubblica, 2024)
The article aims to explore the forms of representation and identity formation among the so-called second generations of migrants in Italy, particularly young Afro-descendants. By considering them as ephemeral cultural artifacts, and through the analysis of digital content created by certain public profiles on social platforms such as TikTok, we can gain a better understanding of the new identity processes embedded in the contemporary Italian social fabric. For these notes on digital ethnography, the extensive philosophical and political tradition of Blackness studies serves as a valuable archive to explore. Additionally, by listening to the lived experiences of two young Black individuals, I found that in opposition to what I call the microphysics of racism, there is a subjectivity aware of representing something new. Something they termed: “New generation”.